2022
DOI: 10.1182/blood.2021014241
|View full text |Cite
|
Sign up to set email alerts
|

Venetoclax synergizes with gilteritinib in FLT3 wild-type high-risk acute myeloid leukemia by suppressing MCL-1

Abstract: BCL-2 inhibition has been shown to be effective in acute myeloid leukemia (AML) in combination with hypomethylating agents or low-dose cytarabine. However, resistance and relapse represent major clinical challenges. Thus, there is an unmet need to overcome resistance to current venetoclax-based strategies. We performed high-throughput drug screening to identify effective combination partners for venetoclax in AML. Overall, 64 anti-leukemic drugs were screened in 31 primary high-risk AML samples with or without… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 40 publications
2
33
0
Order By: Relevance
“…Systematic, high-throughput combination drug screens revealed that MRX-2483 most profoundly and consistently synergizes with the BCL-2 specific inhibitor, venetoclax, and to a lesser extent the pan BCL-2 inhibitors gossypol or obatoclax (48, 49) to provide anti-leukemia activity across a genotypically diverse panel of AML cell lines and primary patient samples. These findings are consistent with recent reports demonstrating synergistic interactions between venetoclax and FLT3, dual FLT3/AXL, or dual MERTK/AXL inhibitors in AML (50-52) and provide the first demonstration of synergy between a dual MERTK/FLT3 inhibitor and venetoclax in AML. Of note, MRX-2843 synergized with venetoclax in the absence of activating FLT3 mutations.…”
Section: Discussionsupporting
confidence: 92%
“…Systematic, high-throughput combination drug screens revealed that MRX-2483 most profoundly and consistently synergizes with the BCL-2 specific inhibitor, venetoclax, and to a lesser extent the pan BCL-2 inhibitors gossypol or obatoclax (48, 49) to provide anti-leukemia activity across a genotypically diverse panel of AML cell lines and primary patient samples. These findings are consistent with recent reports demonstrating synergistic interactions between venetoclax and FLT3, dual FLT3/AXL, or dual MERTK/AXL inhibitors in AML (50-52) and provide the first demonstration of synergy between a dual MERTK/FLT3 inhibitor and venetoclax in AML. Of note, MRX-2843 synergized with venetoclax in the absence of activating FLT3 mutations.…”
Section: Discussionsupporting
confidence: 92%
“…89 Janssen and coworkers screened in vitro 654 antileukemic compounds in combination with VEN in 31 primary samples of high-risk AMLs and observed that gilteritinib exhibited the highest synergy with VEN in WT FLT3 AMLs. 90 Importantly, the VEN+gilteritinib was active in inducing apoptosis of leukemic cell lines and primary AML cells resistant to VEN+AZA. 90 Mechanistically, the VEN+gilteritinib combination decreased phosphorylation of ERK and GSK3B via combined inhibition of FLT3 and AXL, mediating suppression of the MCL1 antiapoptotic protein through induction of its proteasomal degradation.…”
Section: Flt3-mutatedmentioning
confidence: 99%
“… 90 Mechanistically, the VEN+gilteritinib combination decreased phosphorylation of ERK and GSK3B via combined inhibition of FLT3 and AXL, mediating suppression of the MCL1 antiapoptotic protein through induction of its proteasomal degradation. 90 These observations support the evaluation of VEN+gilteritinib as a potential therapeutic regimen for high-risk AML patients with FLT3 WT.…”
Section: Outcomes Of Selected Aml Subtypes Following Venetoclax-based...mentioning
confidence: 99%
See 1 more Smart Citation
“…Of note, combination of venetoclax and gilterinib seems to be highly synergistic in vitro and in mice xenografts through the inhibition of MCL1 and the kinase AXL. 64 This combination will probably be game-changing in the management of FLT3mut AML in the future.…”
Section: Perspectivementioning
confidence: 99%